SOME BACTERIA ISOLATED FROM MARINE PLANKTON AND MUD - GORE, P S (Fishery Technology, 2025)
Fiftyseven bacterial strains isolated from marine plankton and mudfrom the inshore waters of Cochin are described. The flora ofthe plankton was dominated by chromogens while mud sample&failed to produce chromogens. The different strains are dividedinto five arbitrary groups for the convenience of description. Theflora is similar to that of Mandapam (east ccast) while it differedfrom the flora of Calicut (west coast) in tlic paucity of Baci!TusÂ·sp and other sporeformers.